Abdullah Conferred Honorary Degree By UPM. - Bernama
SERDANG, Aug 8(Bernama)-- Former prime minister Tun Abdullah Ahmad Badawi was conferred an Honorary doctorate in agricultural development by Universiti Putra Malaysia(UPM)at its convocation here on saturday.